2013
DOI: 10.4012/dmj.2012-228
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the space for wash materials on sulcus depth reproduction with addition-curing silicone using two-step putty-wash technique

Abstract: Aim of this study was to investigate effects of space thickness and consistency of wash materials on sulcus depth reproduction with silicone impressions, low (L), medium (M), and very high consistency (VH), using two-step putty-wash technique. Impressions were taken from truncated cones with 50-, 100-, or 200-μm-wide sulci, using the combinations L+VH or M+VH and different space thickness for wash materials: 2 mm (ST2), 1 mm (ST1), and approximately 25 μm (ST0.025). Sulcus depth reproduction tended to increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
(19 reference statements)
1
8
0
1
Order By: Relevance
“…Since the presence of high filler content in putty addition silicone material limits this shrinkage 2,9 , the amount of shrinkage occurring in two step addition silicone putty wash impression is mainly influenced by the thickness of light body present in the impression 8,9 . This result is in agreement with other studies which have shown that impression material of thickness 2mm gives better dimensional accuracy and as the thickness of the material increases more than 2mm the dimensional accuracy decreases 8,10,11 . However some authors have mentioned that if the thickness of light body is less than 1mm then also the dimensional accuracy of the impression is affected 11,12 .…”
Section: Discussionsupporting
confidence: 83%
“…Since the presence of high filler content in putty addition silicone material limits this shrinkage 2,9 , the amount of shrinkage occurring in two step addition silicone putty wash impression is mainly influenced by the thickness of light body present in the impression 8,9 . This result is in agreement with other studies which have shown that impression material of thickness 2mm gives better dimensional accuracy and as the thickness of the material increases more than 2mm the dimensional accuracy decreases 8,10,11 . However some authors have mentioned that if the thickness of light body is less than 1mm then also the dimensional accuracy of the impression is affected 11,12 .…”
Section: Discussionsupporting
confidence: 83%
“…6 Hal ini dikarenakan kemampuan dalam mengkombinasikan physical property yang baik, mudah digunakan dan stabilitas dimensi yang baik. 7,8,9 Silikon adisi dikenal sebagai bahan cetak yang baik karena stabilitas dimensinya, namun teknik pencetakan menjadi faktor yang memengaruhi akurasi dimensi. 10 Menurut Hung, dkk pencetakan putty/wash direkomendasikan untuk mengatasi masalah shrinkage polimeritation pada silikon adisi.…”
Section: Pendahuluanunclassified
“…Polyvinyl siloxanes do not present byproduct formation after the polymerization reaction, which is expected to guarantee dimensional stability. It was shown that it remains dimensionally stable for up to 7 days and, also after the preparation of a first cast, it is possible to make a subsequent cast from the same mold 4,8,10 . However, the additional polymerization reaction involves linking a vinyl siloxane in the base material with a hydrogen siloxane via a platinum catalyst, where it is expected to occur some material shrinkage.…”
Section: Introductionmentioning
confidence: 99%
“…Polyvinyl siloxanes are found in different viscosities (from very low to very high viscosity materials), making it possible to use different impression techniques: regular onestep (single phase), putty wash one-step (simultaneous impression technique) and putty wash two-step (reline impression technique) 2,4,8,10,[12][13][14][15][16][17][18][19] . The single phase impression technique employs only a regular body monophase material, which is inserted into an individual tray.…”
Section: Introductionmentioning
confidence: 99%